Circulation of Highly Pathogenic Avian Flu Virus in the Russian Federation in 2014-2015 - V. Yu. Marchenko; I. M. Susloparov; A. V. Shipovalov; V. N. Mikheev; A. B. Ryzhikov (Проблемы особо опасных инфекций, 2016)
Given are the data on the circulation of highly pathogenic flu virus, A/H5, within the last two years. Discussed is the current state of the situation on H5 flu in the territory of the Russian Federation, where during 2014-2015, for the first time since 2010, registered has been the isolation of highly pathogenic flu virus, H5N1 and H5N8 subtypes. It is demonstrated that the territory of Russia plays a significant role in trans-continental transfer of flu viruses by wild birds from South-Eastern Asia into Europe and North America. Moreover, an assumption is made that a continued circulation of highly pathogenic viruses in the territory of the country is quiet possible.